Revealing the community within: valuing the role of local community structures within evidence-based school intervention programmes - McIntyre, Joanna; Knight, Rupert (Springer Verlag, 2016)
Schools and the families they serve are sometimes perceived as deficient and in need of fixing. One response has been the implementation of evidence-based family intervention programmes, which may be highly regulated and prescriptive as a condition of their (often philanthropic) funding. This article seeks to explore and bring to the foreground the often hidden role of the pre-existing, informal community networks with a view to more authentic evaluation of these externally imposed programmes. The article draws on a range of qualitative data reflecting the lived experiences of participants—including parents and other community members—in a family and parenting programme at an English primary school. The analysis uses the work of Tönnies as a theoretical lens. It suggests that while there are tensions caused by the rigid requirements of external programmes, these are overcome in many cases by the highly effective, but often unacknowledged, contributions of the informal aspects of community. It is argued that these operate within and complement the formal programme. Far from subverting the more overt procedures, they actually enable it to function successfully, leading to additional, unanticipated transformations among participants. The article concludes that these organic, often invisible connections need to be identified, documented and nurtured if their full potential is to be recognised and realised when evaluating similar interventions.